2016
DOI: 10.3892/mmr.2016.4848
|View full text |Cite
|
Sign up to set email alerts
|

Poly (I:C) transfection induces mitochondrial-mediated apoptosis in cervical cancer

Abstract: Polyinosinic acid:polycytidylic acid, known as poly (I:C), is an analogue of double‑stranded RNA, which exhibits direct antitumor effects against several types of cancer. The present study aimed to evaluate the role of poly (I:C) in the apoptosis of cervical cancer cells. The HeLa human cervical cancer cell line was used in the present study, and cell apoptosis was determined following poly (I:C) transfection. Furthermore, the mRNA levels of interferon (IFN)‑β, the production of reactive oxygen species (ROS), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…Typhimurium infection ( Figure 2 A and Figure 4 A). These results are consistent with a number of previously published studies showing that poly(I:C) induces ROS production [ 27 , 28 , 29 ]. Stimulation by TLR agonists themselves can induce ROS production; however, ROS are also generated through TLR-induced intracellular signaling pathways.…”
Section: Resultssupporting
confidence: 93%
“…Typhimurium infection ( Figure 2 A and Figure 4 A). These results are consistent with a number of previously published studies showing that poly(I:C) induces ROS production [ 27 , 28 , 29 ]. Stimulation by TLR agonists themselves can induce ROS production; however, ROS are also generated through TLR-induced intracellular signaling pathways.…”
Section: Resultssupporting
confidence: 93%
“…Similar results were obtained by Chen et al [109], who showed that transfection of PolyI:PolyC into HeLa cervical cancer cells induced IFN-β synthesis, formation of reactive oxygen species, causing DNA damage, activation of caspases 3 and 9, and finally apoptosis.…”
Section: Dsrna-based Drugs As Anti-tumor Agentssupporting
confidence: 89%
“…Our study provides a potential link between mitochondrial damage and the activation of PRRs, which subsequently leads to upregulation of type I IFN. Based on the evidence that mitochondrial dysfunction and accumulation of damaged mitochondria are frequently reported in SS patients (Barrera et al, 2021;Rai et al, 2021), we began our study by stimulating SGECs with poly I:C to yield reactive oxygen species (ROS) stress and disruption of mitochondrial potential (Chen et al, 2016;Harashima et al, 2014). We found that poly I:C stimulation resulted in the cytosolic release of mt-dsRNAs, and subsequent PKR phosphorylation and ISG induction.…”
Section: Discussionmentioning
confidence: 99%